INTENSI BERWIRAUSAHA DITINJAU DARI KREATIVITAS DAN KECERDASAN EMOSIONAL - Larisa Yohanna; Harsoyo Dwijo Wijono (Universitas Indraprasta PGRI, 2016)
The creativity and emotional inteliigence provide strong support for intention of entrepreneurship. This study aims to determine whether there is a direct influence either creativity or emotional intelligence towards the intention of entrepreneurship, whether there is an intervention of emotional intelligence that leads to the indirect effect creativity towards the intention of entrepreneurship, and the influence of creativity and emotional intelligence simultaneously towards the intention of entrepreneurship. This study uses a quantitative approach with survey method. Analysis data of hypothesis testing employs a path analysis. Samples were obtained from 154 students taking entrepreneurship courses. The test results prove that there are a direct effect of creativity towars the intention of entrepreneurship by 4.58%, a direct influence of emotional intelligence towards the intention of entrepreneurship by 6.2%, the influence both creativity and emotional intelligence towards the intention of entrepreneurship releases at 15.7%, and the indirect effect of creativity towards the intention entrepreneurial as a result of intervention emotional intelligence by 10.3%, where the effect is greater than the contribution of creativity to the intention of entrepreneurship. Keywords : Intention of Entrepreneurship, Creativity, and Emosional Intelligence.